Sorting based on Urban Heritage and Income: Evidence from the Amsterdam Metropolitan Area - Mark van Duijn; Jan Rouwendal (Tinbergen Institute, 2015)
Urban heritage is often concentrated in conservation areas with a protected status. Previous research argues that urban heritage attracts especially higher educated households who are likely to have higher incomes. The presence of these households may have a further impact on the attractiveness of the neighborhoods concerned, for instance through endogenous amenities like better shops or schools. If this is the case for high income households, conservation areas will have a further impact on the areas attractiveness through the demographic composition of the residential area. In this paper we investigate the interaction between the preference for urban heritage as an exogenous amenity and the preference for areas with a high concentration of high income households as an endogenous amenity. We develop a logit-based sorting model in which different incom e groups interact and estimate it for the Amsterdam metropolitan area. Results show that all employed households highly value conservation areas and prefer to live in areas with a high concentration of high income households. We investigate the impact of urban heritage on house prices and welfare through counterfactual simulations. The disappearance of urban heritage would result in a substantially more suburbanized location pattern of the high income households in the Amsterdam metropolitan area, and to lower welfare for all income groups.
Keywords: R2; J1; Z1; 330; Location choice; urban heritage; sorting models; discrete choice; heterogeneous household preferences; welfare analysis